miRNA expression profile in Behcet patients using colchicine - Eyerci, Nilnur; Balkan, Eda; Keles, Sadullah; Akdeniz, Necmettin (Annals of Medical Research, 2021)
Aim: Behcet’s disease (BD) is a multi-systemic disorder which shows inflammatory vasculitis characteristic with recurrent oral aphthae, eye lesions, and genital ulceration. MicroRNA’s (miRNAs) are small non-coding RNA molecules that play an important role in the regulation of various biological processes. We aimed to determine miRNAs that are thought to be associated with inflammatory processes in BD patients using colchicine in the active period.Materials and Methods: We enrolled 24 patients with BD receiving colchicine treatment and a control group comprising 30 healthy unrelated individuals. We studied with a panel where 377 miRNAs were included in the assay. Results: miR-20a, miR-34a, miR-197, U6snRNA, miR-205, miR-222, miR-296, miR-302a, miR-302c, and miR-372 were observed up-regulated in BD. miR-518b, miR-874 were found down-regulated within the patients. These miRNAs are known to play a role in cancer-related pathways.Conclusion: In patients treated with colchicine, the change in the expression of these miRNA may give an idea of the effect on the progression of the disease. However, patients in the active period also require further studies to fully understand the role and mechanism of action of the drug.
Keywords: Behcet disease; colchicine; microRNA